A Bacillus cereus outbreak in Kulon Progo Hospital, November 2020 - Meutia Fildzah Sharfina (BKM Public Health and Community Medicine, 2021)
Objective: On November 4th, 2020 RSUD Wates and RST COVID-19 reported to the Kulon Progo District Health Office a suspected food poisoning outbreak on health workers after a served lunch menu on November 3rd, 2020. This study aimed to investigate to confirm the outbreak, source of food poisoning and to develop the recommendation. Method: A retrospective case control study was used with active case finding. Case is people who have diarrhea and one or more symptoms of vomiting, headache, fever, nausea, abdominal pain or other symptoms after consuming the lunch menu from the catering during the lunch hour on November 3, 2020 at RSUD Wates and RST COVID-19 Kulon Progo. Results: A total 85 workers, 28 workers (AR=32,9%) were ill. The incubation period was around 2-32.5 hours. The predominant symptoms were diarrhea (21,2%) and fever (17,6%). The statistical test results showed rice (p value= 0.027; CI 1.4876) and sambal (p value= 0.014; CI 1,6741) are related to the event (p value < 0.05). Based on the incubation period, symptom and type of food, the investigation team suspected Bacillus cereus as a causal factor of the food poisoning outbreak. Conclusion: The food poisoning outbreak most likely was caused by Bacillus cereus. Therefore we recommend to strengthen the intervention community health education about safe food processes.